2021
DOI: 10.1027/1015-5759/a000602
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Dark Personalities

Abstract: Abstract. Consensus is emerging that the constellation of dark personalities should include the sadistic personality. To build a four-factor measure, we modified and extended the Short Dark Triad (SD3) measure to include sadism. A series of three studies yielded the Short Dark Tetrad (SD4), a four subscale inventory with 7 items per construct. Study 1 ( N = 868) applied exploratory factor analysis (EFA) to a diverse 48-item pool using data collected on MTurk. A 4-factor solution revealed a separate sadism fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
150
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(162 citation statements)
references
References 120 publications
(199 reference statements)
11
150
0
1
Order By: Relevance
“…Last, the narcissism scale from the SD4 revealed stronger than expected correlations with physical and verbal aggression (rs = .18 and .30, both expected rs = .10) and antagonism (r = .44, expected r = .30, pdiff < .05, psTOST ≤ .97). Paulhus et al (2020) found similar correlations with neuroticism, agreeableness, and extraversion.…”
Section: Narcissismmentioning
confidence: 60%
“…Last, the narcissism scale from the SD4 revealed stronger than expected correlations with physical and verbal aggression (rs = .18 and .30, both expected rs = .10) and antagonism (r = .44, expected r = .30, pdiff < .05, psTOST ≤ .97). Paulhus et al (2020) found similar correlations with neuroticism, agreeableness, and extraversion.…”
Section: Narcissismmentioning
confidence: 60%
“…Apart from the first three traits, Sadism can predict insensitivity to the suffering of others, and can also predict insensitivity when to "strike back" when threatened (Buckels et al, 2013). Sadism also has shown a unique relation to Internet Trolling (Buckels et al, 2013) and to sexuality (Paulhus et al, 2020). The unique aspect of Sadism is that the individual enjoys the suffering of others.…”
Section: Dark Personality Traitsmentioning
confidence: 99%
“…We also administered the Narcissism subscale from the Short Dark Triad (Jones & Paulhus, 2014) and the Mach and Psychopathy subscales from the Short Dark Tetrad (Paulhus et al, 2020). Because we did not have any hypotheses for these three scales, their results are reported in the supplemental online material (Table S17).…”
Section: Resultsmentioning
confidence: 99%
“…That is, subclinical psychopathy focuses on the features that are nonoverlapping with Mach and narcissism. Generally, in the tradition of the Dark Triad research, the aim has been to create relatively unidimensional scales that isolate the unique features of Mach and psychopathy (e.g., Paulhus et al, 2020). Although established psychopathy scales that are used in Dark Triad research might also overlap with narcissism and sadism scales, we did not develop new narcissism and sadism measures because doing so would have diverted the focus and gone beyond the scope of the current research.…”
Section: The Current Research the Current Researchmentioning
confidence: 99%